The Role Of Gamification In English Language Teaching: A Literature Review - Ni Putu Wulantari; Azhariah Rachman; Mike Nurmalia Sari; Lulu Jola Uktolseja; Agus Rofi'i (Journal on Education, 2023)
This literature review examines the impact of gamification in English language teaching (ELT) on motivation, engagement, and learning outcomes. Gamification, the integration of game elements into education, has gained attention as a promising approach to enhance language learning. The findings reveal that gamification positively influences student motivation in ELT. Elements like points, leaderboards, and rewards create a sense of achievement and intrinsic motivation. Engaged students are more likely to persist and participate actively in language learning. Gamification promotes active learning and engagement, with interactive activities involving vocabulary acquisition, grammar practice, and language production. It provides a safe space for students to experiment, apply knowledge, and develop linguistic skills. Collaboration and social interaction are fostered through gamification, encouraging teamwork and peer feedback. This enhances language and interpersonal skills. Immediate feedback and progress tracking in gamification offer valuable learning opportunities. Students receive real-time feedback and monitor their progress, enabling adjustments in learning strategies. However, implementing gamification in ELT faces challenges such as technology constraints and pedagogical considerations. Striking a balance between engagement and curriculum objectives is crucial. Teacher training and professional development are necessary. In conclusion, gamification plays a significant role in ELT by enhancing motivation, engagement, collaboration, and active learning. Despite challenges, embracing gamification and its best practices